A nonlinear dynamic vibration model of defective bearings – The importance of modelling the finite size of rolling elements. (February 2015) - Moazen Ahmadi, Alireza; Petersen, Dick; Howard, Carl
Abstract: This paper presents an improved nonlinear dynamic model of the contact forces and vibration response generated in defective rolling element bearings. The improvement comes about by considering the finite size of the rolling elements which overcomes the limitations exhibited by previous models caused by the modelling of rolling elements as point masses. For line spall defects, a low frequency event occurs in the measured vibration response when a rolling element enters the defect. Previous models were not able to accurately predict this event without making the simulated and actual defect geometries significantly different. Comparisons between the proposed model, previous models and experimental results are carried out to show that the low and high frequency events are more accurately predicted. This analysis identifies and explains the mechanisms leading to inaccuracy of the previous models. The model developed here can be used to aid in the development of new diagnostic algorithms. Highlights: We present a nonlinear multi-body dynamic vibration model of a defective bearing. We show the importance of modelling the finite size of the rolling elements. We demonstrate improvement over models that consider rolling elements as point masses. We show good agreement between simulated and experimental results. We identify and explain the cause of inaccurate predictions of point mass models.